Perencanaan Sistem Elektrikal pada Apartemen Menara One Surakarta - Ulil Albab AlFaruq; Budi Santoso; Chico Hermanu B Apribowo (Mekanika: Majalah Ilmiah Mekanika, 2018)
This paper presents the design of electrical system in Menara One apartment. Electrical system calculation based on PUIL 2000 method. The conductor uses 1.25 times the nominal current as a safety factor. The calculation of voltage drop based on total load, length, and area of conductor. Total load is calculated from apartment room and apartment utility load. Total load results are used to determine generator capacity and transformer. The load capacities apartment rooms are 2.2 kVA for type 1 and 3.5 kVA for type 2-6. The total of utility load is 215.8 k VA. The maximum installed room for the apartment is 982.31 kVA with voltage drop from the farthest panel to the LVMDP is 1.89%.